Development of a Job Satisfaction Model Using Soft System Methodology (SSM) Analysis at the Jakarta National Police Education and Training Center - Rusdian, Dadan; Fitriani, Rachma (International Journal on Advanced Science, Education, and Religion, 2023)
This study aims to identify and explain the factors that influence job satisfaction, namely charismatic leadership, empowerment and respect at the Women's Police School (Sepolwan) at the Jakarta Police Education and Training Center. From the results of data processing using the SSM method, it is concluded that 1) charismatic leadership has an influence on job satisfaction in terms of realizing the pattern of charismatic leadership needed by the organization, 2) empowerment can be realized through improving communication channels (both formal and informal) which are currently lacking seen to have an influence on employee job satisfaction, 3) respect influences job satisfaction because it can clarify the definition of job satisfaction itself and make leader-member interaction more conducive. For this reason, it is recommended that agencies maximize the function of the Work Culture Task Force and hold various activities that can increase interaction and two-way communication between superiors and subordinates, as well as provide an informal space for conveying members' opinions so that the definition of job satisfaction of each employee can be more clearly seen in behaviour, so that job satisfaction can be more easily increased